2014
DOI: 10.5664/jcsm.3360
|View full text |Cite
|
Sign up to set email alerts
|

Influence and Predicting Variables of Obstructive Sleep Apnea on Cardiac Function and Remodeling in Patients without Congestive Heart Failure

Abstract: Study Objective: Obstructive sleep apnea syndrome (OSAS) has been considered to be an important predisposing factor for cardiovascular disease. This study aims to investigate the impact of OSAS on cardiac function and remodeling in patients without congestive heart failure. Methods: A total of 79 patients with sleep disordered breathing, preserved systolic function, and normal pro-brain natriuretic peptide level were enrolled. Sixty-fi ve patients were classifi ed to have moderate to severe OSAS (apnea-hypopne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 50 publications
2
26
1
1
Order By: Relevance
“…Six cross-sectional studies investigating patients referred for a sleep evaluation reported a positive association between the aortic root diameter and parameters of OSA severity (either AHI or oxygen desaturation index (ODI)) [45,[48][49][50][51][52]. Notably, one study found an association with AHI in rapid eye movement sleep only where the severity of OSA becomes greater, partly due to a decreased respiratory muscle tone [52]. Another study reported this association in patients with hypertrophic cardiomyopathy [48].…”
Section: General Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Six cross-sectional studies investigating patients referred for a sleep evaluation reported a positive association between the aortic root diameter and parameters of OSA severity (either AHI or oxygen desaturation index (ODI)) [45,[48][49][50][51][52]. Notably, one study found an association with AHI in rapid eye movement sleep only where the severity of OSA becomes greater, partly due to a decreased respiratory muscle tone [52]. Another study reported this association in patients with hypertrophic cardiomyopathy [48].…”
Section: General Populationmentioning
confidence: 99%
“…Most of the studies investigated the association between OSA and the aortic root diameter [44][45][46][47][48][49][50][51][52]. Six cross-sectional studies investigating patients referred for a sleep evaluation reported a positive association between the aortic root diameter and parameters of OSA severity (either AHI or oxygen desaturation index (ODI)) [45,[48][49][50][51][52]. Notably, one study found an association with AHI in rapid eye movement sleep only where the severity of OSA becomes greater, partly due to a decreased respiratory muscle tone [52].…”
Section: General Populationmentioning
confidence: 99%
“…We controlled for a number of covariates that are known to be associated with cognitive function ( 13 ) and sleep difficulties ( 16 ). Several covariates were taken from the respondent’s baseline interview including age in years; gender coded as 1 = female, 0 = male; race coded as 1 = white, 0 = nonwhite; ethnicity coded as 1 = Hispanic, 0 = non-Hispanic; marital status coded as 1 = married or living with a partner, 0 = unmarried (never married, widowed, and divorced); education coded as years of schooling (0–17 years or more); and total self-reported financial assets coded by quartile (1 = <$55,000, 2 = $55,000 to $182,999, 3 = $183,000 to $464,999, and 4 = $465,000 or higher).…”
Section: Methodsmentioning
confidence: 99%
“…Several recent studies showed that short-term CPAP treatment can improve cardiac function and structure, however further studies are needed to confirm its theoretical benefit on stroke risk. (54)(55)(56)(57)(58)(59) Studies have reported an association between SBD and carotid atherosclerosis. Interestingly asymptomatic carotid stenosis is associated with central, but not obstructive apneas.…”
Section: Pathophysiologymentioning
confidence: 99%